Interiors and their decoration in the traditional mud-brick architecture of the Najd region of Saudi Arabia and the factors that have influenced the development of interior decoration and spatial organization - Al-Anbar, Ali Saleh (The University of Edinburgh, 1999)
This study is an attempt to analyse the early traditional interiors and decoration of mud -brick buildings in the Najd region of Sa`udi Arabia. It also aims to discuss the factors which have had effect on the developments of both the interiors and types of decoration in these buildings. The focus of the study was on the political and socio- economic developments in the region following the establishment of the First Sa'udi State from 1745 until 1930s. Due to a combination of the centralisation of decision -making and the government's financial support for modernisation, most traditional mud -brick settlements fell into disrepair and were replaced by new modern concrete settlements, based on Western designs. However, these settlements, Western models of urban development, have proved inadequate and have failed to solve the local problems of urban design and planning. This is due to the fact that they are not tailored to the specific social and political environment of an `Arab Muslim cultural system. So Najdians have begun to long for the traditional culture and early mud -brick interior forms and design. Towards the end of the 1980s an awareness of the need to preserve and promote elements of traditional culture developed, not only in the Najd but throughout the Kingdom of Sa'udi Arabia. This cultural re- evaluation has extended to traditional architecture and includes a re- appraisal of the traditional interiors and decoration of those mud -brick buildings that are still extant. This re- awakening can also be seen in the desire for modern concrete buildings to be redesigned so something of the traditions of interior decoration and design can be retrieved. The new cultural re- evaluation of the traditional heritage poses three important questions. Firstly, what is the traditional mud -brick interior and what are its contexts ? Secondly, what are the cultural forces that have given rise to urban architectural development in the traditionally -built forms, interior spaces and decoration ? Thirdly, why have the people of the Najd reverted, even in their new concrete buildings, to the interiors and decoration of earlier times? This study was motivated by a desire answer these questions. This necessarily touches upon the changes in Sa`udi Arabia: social, political and economic. This study is based on ethnographic, architectural and ethno-archaeological fieldwork relating to the ancient mud -brick buildings of the Najd. Data was collected from historical sources, site information as well as from interviews with people living in the region. All this is illustrated by drawings and photographs. This thesis consists of three parts. The first part classifies the traditional building materials and techniques of building construction, the mud-brick settlement and its buildings types. The second part analyses the interior architectural features of a typical residential building, the decorative elements and techniques of ornamentation, the structural elements and their decoration, and the interior vocabulary. The third part analyses the factors affecting development of decoration and space organisation.
A study of the interiors and their decoration in the traditional mud-brick architecture of the Najd region of Saudi Arabia and the factors that have influenced the development of interior decoration and spatial organization